2021
DOI: 10.1186/s12912-021-00630-2
|View full text |Cite
|
Sign up to set email alerts
|

Psycho-social components determining the strategies of coping with stress in undergraduate Polish nursing students

Abstract: Background In order for the nursing students to fully benefit from the clinical experience, it is necessary for them to be able to handle education-related stress. It is important to establish the importance of personal resources and social determinants, that influence coping strategies in stressful situations. Methods The cross-sectional study was conducted among 307 nursing students. The study research tools: Perceived Stress Scale (PSS-10), Life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 50 publications
2
10
0
Order By: Relevance
“…A study conducted by Bodys-Cupak et al among Polish nursing students [68] showed a high and average level of optimism in the majority of the study participants. Those with a higher level of dispositional optimism coped with stress and negative emotions significantly more frequently.…”
Section: Discussionmentioning
confidence: 77%
“…A study conducted by Bodys-Cupak et al among Polish nursing students [68] showed a high and average level of optimism in the majority of the study participants. Those with a higher level of dispositional optimism coped with stress and negative emotions significantly more frequently.…”
Section: Discussionmentioning
confidence: 77%
“…The study conducted by Bodys-Cupak et al showed a high and average level of optimism in a majority of the nursing students participating in the research. Those with a higher level of dispositional optimism coped with stress significantly more often by active coping, positive redefinition, planning, acceptance and seeking emotional and instrumental support [ 54 ]. A study by Joseph et al [ 55 ] showed similar findings.…”
Section: Discussionmentioning
confidence: 99%
“…The research questionnaires used in the study were: Perceived Stress Scale (PSS10), Generalized Self-Efficacy Scale (GSES), Self-Esteem Scale (SES), Life Satisfaction Scale (SWLS), Life Orientation Test (LOT-R) and an inventory for the assessment of the clinical learning environment (CLEI-19) and a questionnaire developed by members of the research team, which included, among others, questions about sociodemographic variables. Some of the research tools were described in detail in the article “Psycho-social components determining the strategies of coping with stress in undergraduate Polish nursing students” published in BMC Nursing [ 19 ]. Below is just a general presentation of the research tools used.…”
Section: Methodsmentioning
confidence: 99%
“…These positive and negative effects of stress are inherently related to personal resources and, therefore, to the ability of students to cope with stress [ 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%